Enhancing Pedagogical Skills and Industry Knowledge for Maritime Instructors through Applied Management Studies - April Gunawan; Tri Cahyadi; Larsen Barasa; Jay Singgih; Wardoyo Dwi Kurniawan; Geboy Geboy (Digital Innovation : International Journal of Management, 2024)
This study examines the effectiveness of enhancing teacher training and development programs for maritime instructors by focusing on improving both pedagogical skills and industry knowledge. The research explores applied management strategies in the fields of port, shipping, and logistics, aligning them with industry-specific educational needs. Qualitative perspectives from 5 maritime professionals, 5 lecturers, and 5 graduates working in maritime sectors were analyzed through descriptive analysis. The study aims to understand how maritime instructors can effectively integrate technical, promotional, marketing, and innovative skills into their teaching practices to better prepare students for the maritime industry. The data collection was conducted through structured interviews, observations, and focus group discussions. Findings indicate that improving teacher training not only enhances instructor competencies but also bridges the gap between maritime education and industry requirements. Key indicators include the effectiveness and efficiency of the training programs, with a performance score of 9/10 based on qualitative assessment. The paper discusses the implications for maritime vocational education, emphasizing the need for continuous improvement in instructor development. The study concludes with recommendations for further enhancing maritime teacher training programs by incorporating modern management practices and technological advancements to ensure that maritime education stays relevant to industry demands.